A new deal for the climate? Lessons from the Inflation Reduction Act - Pia Kauer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2025)
The Inflation Reduction Act (IRA), passed under the Biden administration in August 2022, is the biggest US climate bill to date. Its focus on subsidy-driven decarbonization incentives marks a potential turning point in US industrial policy and might prevent its repeal under the upcoming Trump administration. This paper closely examines how the IRA aims to address the crisis of US capitalism with a particular emphasis on its ecological, geopolitical, and social objectives. Central to the IRA are strategies for decarbonizing the power and transport sectors, enhancing US competitiveness in the clean energy and battery industries, and linking subsidies to workers' rights. Despite its transformative potential to advance renewable energy and generate 'green' jobs, the IRA also includes concessions to the fossil fuel industry and incorporates protectionist measures that could heighten international tensions, especially with China. This analysis situates the IRA within the broader context of the crisis of post-Fordism and explores its role in a potential 'state-interventionist turn' towards a greener capitalism, while critically assessing its adequacy in addressing the urgency of climate action.
Keywords: H23; J58; O25; P18; Q42; Q48; Q54; 330; Inflation Reduction Act; Industrial Policy; Decarbonization; Energy Transition; Regulation Theory